Diastomatomyelia- A Case Series - Das, Uddalok; Pandit, Narayan (Nepal Journal of Neuroscience, 2023)
Diastematomyelia also called a split cord syndrome is a rare clinical entity. A group of concealed spinal dysraphisms includes this unusual congenital spinal cord defect known as diastematomyelia. The condition is characterized by a sagittal split of the spinal cord,conus medullaris, or filum terminale. There is often a fibrous, boney, or cartilaginous septum identified by dividing the two cords. It is frequently associated with other congenital anomalies of the spine and the cord. Presentation is varied from asymptomatic to lower back pain, lower extremity weakness, and spinal cord dysfunction. Imaging plays a vital role in the diagnosis. We present a series of 2 cases of diastematomyelia along with imaging features. One of the patients is also a case of Jarcho Levine syndrome (JLS) making it the eighth case in world medical literature to report a case of JLS with diastematomyelia.